DNA delivery into plant tissues using carbon dots made from citric acid and β-alanine - Shivashakarappa, Kuber; Marriboina, Sureshbabu; Yadegari, Zeinab; Paduri, Vikas Reddy; Sachan, Ritesh; Dumenyo, Korsi; Taheri, Ali (Frontiers in Chemistry, 2025)
Agriculture and food security face significant challenges due to population growth, climate change, and biotic and abiotic stresses. Enhancing crop productivity and quality through biotechnology is crucial in addressing these challenges. Genome engineering techniques, including gene cassette delivery into plant cells, aim to meet these demands. However, conventional biomolecule delivery methods have limitations such as poor efficacy, low regeneration capability, and potential cell damage. Nanoparticles, known for their success in drug delivery in animals, hold promise as DNA nanocarriers in plant sciences. This study explores the efficacy of carbon dots (CDs), synthesized rapidly and cost-effectively from citric acid monohydrate and β-alanine using a microwave-assisted method, as carriers for plasmid DNA delivery into plant tissues. The detailed characterization of carbon dots, evaluation of their binding ability with plasmid DNA, and phytotoxicity assessments were systematically conducted. The delivery and expression of plasmid DNA were successfully demonstrated in canola leaves via needleless syringe infiltration and in soybean root cells and protoplasts through passive diffusion. Additionally, the particle bombardment method facilitated the efficient delivery of plasmid DNA of varying sizes (4 kb, 11 kb, and 17 kb) into onion epidermal cells, as well as the successful delivery of plasmid DNA containing the GUS reporter gene into soybean embryos, using carbon dots as a binding agent between plasmid DNA and tungsten microcarrier. To our knowledge, this is the first study to report the use of carbon dots as a substitute for spermidine in such applications. Overall, our research presents a rapidly synthesized, cost-effective platform for efficient plasmid DNA delivery, establishing a foundation for using carbon dots as carriers for CRISPR and RNAi constructs in gene knockout and knockdown applications in plant tissues, with a comparison of their transformation efficiency against traditional delivery techniques.